POTENSI BEBERAPA MIKROBA PEMACU PERTUMBUHAN TANAMAN SEBAGAI BAHAN AKTIF PUPUK DAN PESTISIDA HAYATI - Hanudin Hanudin; Kurniawan Budiarto; Budi Marwoto (Jurnal Penelitian dan Pengembangan Pertanian, 2018)
Consumer demands on safe agricultural products have made the shifting of the production system to be more environmental friendly. An attempt to reduce or totally substitute chemical fertilizers and pesticides on agricultural production process was through the utilization of potential microbes. The purpose of the study was to provide information on potential microbial species that can be used as active ingredients of biofertilizers and biopesticides. The mechanisms of action have been studied, both directly and indirectly, in protecting the plant from pest and disease attacks. Several of these microbes also functioned as decomposer that might improve soil characteristic and nutrient availability for the crops. The Indonesian Agency for Agricultural Research and Development for has released formulated biopesticides and bio fertilizers with the active ingredients isolated from agricultural production centers. The application of these biopesticides and biofertilizers have been effectively controlled important diseases in horticultural crops, i.e. Bio Nutri-V could suppress white rust disease (Puccinia horina Henn) 32.15% in chrysanthemum and increased 25% and 34% harvestable products in chrysanthemum and potato, respectively, compared with synthetic fungicide. The utilization of biopesticides and biofertilizers is expected to improve the competitiveness of national agricultural commodities by utilizing natural resources to support highly competitive and sustainable agricultural industries.Keywords: Microbes, biofertilizer, biopesticide, vegetable, ornamentals, horticulture. AbstrakTuntutan konsumen terhadap keamanan produk pertanian menuntut pula perlunya proses produksi dilakukan secara ramah lingkungan. Salah satu upaya untuk mengurangi atau mensubstitusi penggunaan pupuk dan pestisida kimia sintetik ialah memanfaatkan mikroba. Makalah ini membahas spesies mikroba yang berpotensi dan dapat dijadikan sebagai bahan aktif pupuk dan pestisida hayati. Berbagai spesies mikroba dari kelompok cendawan dan bakteri telah berhasil diisolasi dan dievaluasi keefektifannya sebagai bahan aktif pupuk dan pestisida hayati yang efektif. Mikroba pemacu pertumbuhan tanaman dengan mekanisme langsung maupun tidak langsung mampu menginduksi pertumbuhan tanaman dan beberapa mikroba juga berfungsi sebagai dekomposer, sehingga membantu penyediaan unsur hara bagi tanaman. Badan Litbang Pertanian telah menghasilkan beberapa formulasi pupuk hayati dan biopestisida dengan bahan aktif mikrobe yang diisolasi dari sentra produksi pertanian. Aplikasi pupuk dan pestisida hayati tersebut efektif mengendalikan penyakit penting tanaman hias, seperti Bio Nutri- V dapat menekan perkembangan penyakit karat putih (Puccinia horina Henn) pada krisan 32,2% dan mempertahankan hasil panen kentang dan krisan masing-masing 25% dan 34% dibandingkan dengan aplikasi fungisida kimia sintetik. Pengembangan pupuk dan pestisida hayati yang dihasilkan diharapkan dapat meningkatkan daya saing komoditas pertanian melalui sistem produksi ramah lingkungan dengan memanfaatkan sumber daya alam secara optimal guna mendukung industri pertanian berdaya saing dan berkelanjutan.Kata kunci: Mikroba, pupuk hayati, biopestisida, sayuran, tanaman hias, hortikultura.